Bridging Ethics and Performance: Eco-Product Innovation as a Mediator of Environmental Ethics and Sustainable Performance - Priyanwada Wanigasooriya (Journal of Advanced Research in Social Sciences and Humanities, 2025)
Aim: This study aims to explore the relationship between environmental ethics, and sustainable performance. Additionally, the mediating effect of eco-process innovation, eco-product innovation and eco-management innovation on sustainable performance among manufacturing sectors of Sri Lanka was explored. Methodology: Drawing with stakeholder theory, PLS-SEM, was used to analyse the quantitative data gathered from 388 managers and staff members in a subset of Sri Lankan manufacturing enterprises. Findings: The results show that environmental ethics has positive significance on eco-process innovation, eco product innovation and eco-management innovation. However, mediating effect of eco-process innovation between environmental ethics and sustainable performance. Furthermore, mediating effect of eco-product innovation between environmental ethics and sustainable performance. Similarly, mediating effect of eco-management innovation between environmental ethics and sustainable performance. Implications/Novel Contribution: In practice, it provides a clear path for managers and policymakers to plan how to allocate resources in the best way that prioritizes integrated eco-innovation to advance both ecological stewardship and competitive advantage.